Review Article: Hawai'i's Cesspool Problem: Review and Recommendations for Water Resources and Human Health. (5th January 2021) - Mezzacapo, Michael; Donohue, Mary J.; Smith, Celia; El‐Kadi, Aly; Falinski, Kim; Lerner, Darren T.
Abstract: Cesspools as onsite sewage disposal systems (OSDS) are widespread in the Hawaiian Islands and of concern due to their lack of primary treatment and direct discharge of pathogens and nutrients into groundwater. Approximately 88, 000 cesspools in Hawai'i release nearly 55 million gallons per day (mgd) of sewage into the ground. Here, we review the status of wastewater pollution, with an emphasis on cesspools, and associated impacts to water resources, nearshore ecosystems, and human health. We present evidence supporting the creation of a cesspool conversion plan, highlighting the need to upgrade cesspools. Knowledge gaps in areas such as hydraulic/hydrologic modeling and technological limitations in identifying specific wastewater sources present barriers to addressing cesspool challenges. We show many of these constraints can be diminished. For example, limitations in identifying specific sources from wastewater indicators using %N and δ 15 N can be reduced with available land‐use information and potential pollution sources to clarify concentration and isotopic data. Resource management presents many challenges, including recognition of diverse societal views and values. To overcome discrepancies in available data, and varying societal values, the use of transparent, adaptable framework methods such as "structured decision‐making" offers approaches for problem solving. Such frameworks are consistent with a holistic management approach to OSDS that couple the natural and social sciences in identifying and addressing barriers to reduce negative impacts. Maintaining momentum through adoption of clearly articulated short‐, medium‐, and long‐term achievement benchmarks associated with such a management approach is recommended.